2018
DOI: 10.1111/jonm.12650
|View full text |Cite
|
Sign up to set email alerts
|

Developing nursing leadership talent-Views from the NHS nursing leadership for south-east England

Abstract: Aim This article explores the views of current nursing leaders in the National Health Service on the actions and resources that are required to develop and maintain nursing leadership talent. Background Although there is considerable talent and expertise within the nursing leadership community, numerous unfilled vacancies and gaps have been identified in competence and capability, with a national analysis indicating that nearly a third of National Health Service director posts are filled by interim appointment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…strategies and equally broadly examine the former's individual goals and needs. Moreover, some researchers stressed the importance of timely and organized support of talented candidates combined with their internship and the more personalized support of their role to develop their diverse skills [52]. On the other hand, Leggat et al concluded that T.M.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…strategies and equally broadly examine the former's individual goals and needs. Moreover, some researchers stressed the importance of timely and organized support of talented candidates combined with their internship and the more personalized support of their role to develop their diverse skills [52]. On the other hand, Leggat et al concluded that T.M.…”
Section: Developmentmentioning
confidence: 99%
“…strategies aim to explore talents among the entire personnel, regardless of the employment level, even in the case of those potentially employed [46]. Finally, some researchers support that both the standardization of the networks of the candidate talents and the holistic team approach in their training is essential for the acquisition of the necessary supplies required by their position [52].…”
Section: Succession Planningmentioning
confidence: 99%
“…The other methods included a case study, an exploratory study, and a descriptive study with a mixed methods approach, with one study each (8.3%). Regarding the strategies for the development of nurses' leadership in health services recommended and used in the studies, the leadership development programs (LDP) stood out (A3 17 , A5 19 , A6 20 , A8 11 , A9 22 , A10 23 , A11 24 ), with some programs focusing on succession planning (A3 17 , A9 22 , A11 24 ), coaching and mentoring (A2 16 , A3 17 , A4 18 , A9 22 , A10 23 , A11 24 , A12 25 ), permanent and continuing education (A7 21 , A8 11 ), and workshops (A1 15 , A12 25 ). It is important to mention that not all studies applied the recommended strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Additional healthcare leadership barriers identified less frequently for Malta and Greece included a lack of leadership skills, lack of mentoring and networking, lack of confidence and lack of flexible working environment (Kalaitzi et al, 2019). A lack of perceived support, opportunities to gain financial or board-level experience, attend leadership training or have mentorship often due to workload distribution were barriers to preparing director of nursing leaders in England (Cabral et al, 2019). Similarly, nurse leaders in Malta and the Republic of Ireland identified a lack of leadership preparation, limited opportunities and heavy workloads as barriers to nurse leadership development (Hughes et al, 2019(Hughes et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%